Profiling Communication Ability in Dementia (P-CAD): Development and Validation of a Functional Cognitive-Communication Assessment - DOOLEY, SUZANNA MARIA (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2020)
Introduction: Cognitive communication difficulties are characteristic of dementia with negative impact. (Bayles and Tomoeda, 2007, Hickey and Bourgeois, 2018). There is a perception that little can be done to help communication and clinicians have few options to evaluate functional and retained communication skills in dementia. Research suggests that early management of communication difficulties can reduce the negative impact of communication impairment and improve quality of life (Yorkston et al., 2010, Hickey and Bourgeois, 2018). The purpose of this study was to develop and validate the P-CAD with the objective of providing clinicians with a much needed psychometrically sound assessment for people with dementia. Method: The P-CAD was developed and refined with expert opinion, comprehensive feedback from user groups and a pilot study with speech and language therapists (SLTs). Two studies informed the development of the P-CAD; a scoping review of available cognitive communication assessments for people with dementia and a practice survey of SLTs working in dementia management. One hundred people with dementia and their communication partners were recruited over a 12-month period. The P-CAD was validated against MMSE-2, Global Deterioration Scale (GDS) and Functional Linguistic Communication Inventory (FLCI). Inter-rater reliability and sensitivity to change over time (3 months) were also tested on a subgroup of individuals. Participants with dementia were at different stages of dementia and presented with a range of dementia subtypes. Results: Statistically significant correlations were found between P-CAD scores, MMSE-2 scores (r=0.830, p<0.001) and FLCI scores (r=0.863, p<0.001). There were no significant changes over time in any of the 3 scales for the participants (N=12) who completed follow-up measures. Inter rater reliability for the P-CAD (N=20) was strong between raters for all measures; GDS (ICC=0.969, p<0.001); MMSE-2 (ICC=0.997, p<0.001); FLCI (ICC=0.999, p<0.001); P-CAD (ICC=0.981, p<0.001). Findings confirm statistically significant differences (P<0.001) in MMSE-2 scores (the participant's cognitive level) and GDS levels across the different P-CAD communication support levels. Conclusions: The P-CAD is a valid and reliable cognitive communication assessment, appropriate for use with people across all subtypes and stages of dementia. P-CAD determination of levels of communication support are sensitive to the stage of dementia (GDS) and level of cognitive impairment as measured by the MMSE-2. It facilitates evaluation of functional communication abilities of people with dementia, with a specific focus on conversational skills. It guides intervention, providing measurement of change over time. It is now ready for use in clinical practice, informing interventions aimed at improving conversations between people with dementia and their communication partners.
APPROVED
Keywords: Dementia; Communication; Assessment